Synthesis, microstructural refinement, and shielding optimization of Gd2O3-reinforced AISI 316L stainless steel: a multi-dimensional integration assessment for targeted protection applications - Yayla, Nihal; Albayrak, Muhammet Gokhan; Guler, Omer; Baykal, Duygu Sen; Alkarrani, Hessa; ALMisned, Ghada; Tekin, H. O. (Iop Publishing Ltd, 2025)
This study investigates the multi-dimensional effects of increasing Gd2O3 reinforcement on the structural, mechanical, and gamma-ray shielding properties of AISI 316L stainless steel composites. Samples with varying Gd2O3 content (1%, 5%, 10%, and 20% by weight) were synthesized and characterized through x-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) to assess the microstructural changes and homogeneity of Gd2O3 dispersion after mechanical milling. The addition of Gd2O3 significantly enhanced the gamma-ray shielding properties, with the mass attenuation coefficient (MAC), linear attenuation coefficient (LAC), and half-value layer (HVL) improving as the Gd2O3 content increased, particularly in low to moderate photon energy ranges. Simultaneously, the elastic modulus exhibited an inverse relationship, decreasing with higher Gd2O3 content due to the lower stiffness of gadolinium compared to iron. Transmission factor (TF) values also decreased, indicating enhanced photon attenuation with higher Gd2O3 content across various thicknesses. The experimental characterization confirmed improved Gd2O3 dispersion and material uniformity after mechanical milling, contributing to the composites' superior radiation shielding performance. It can be concluded that Gd2O3-reinforced AISI 316L stainless steel composites offer a promising balance between enhanced radiation shielding properties and reduced mechanical stiffness, making them ideal candidates for applications requiring efficient and adaptable radiation protection especially for portable and non-structural shielding applications.
Keywords: Gd2O3; stainless steel; XRD; radiation shielding; elastic modulus